Pengaruh Debt To Equity Ratio dan Current Ratio Terhadap Net Profit Margin pada Koperasi Jasa Sawit Sejahtera Desa Titian Resak Kecamatan Seberida Kabupaten Indragiri Hulu - Aris Triyono; Suwaji Suwaji; Anisyah Anisyah; Novriyani Novriyani (J-MAS (Jurnal Manajemen dan Sains), 2021)
Financial Ratio Analysis is an analytical tool used to assess the company's financial performance. One of the profitability ratio analysis is Net Profit Margin. To find out the level of success or failure of the Net Profit margin, it is necessary to calculate the ratio analysis, such as the Debt to Equity Ratio and the Current Ratio. The research locations used as research objects are In The Koperasi Jasa Sawit Sejahtera Desa Titian Resak Kecamatan Seberida Kabupaten Indragiri Hulu. The purpose of the study was to determine the effect of the Debt to Equity Ratio and Current Ratio simultaneously on the Net Profit Margin at Koperasi Jasa Sawit Sejahtera Desa Titian Resak Kecamatan Seberida Kabupaten Indragiri Hulu. To find out the Partial Effect of Debt to Equity Ratio on Net Profit Margin in the Koperasi Jasa Sawit Sejahtera Desa Titian Resak Kecamatan Seberida Kabupaten Indragiri Hulu. To find out the partial effect of the Current Ratio on the Net Profit Margin in the Koperasi Jasa Sawit Sejahtera Desa Titian Resak Kecamatan Seberida Kabupaten Indragiri Hulu. The research method used is, Quantitative Method. The data used is secondary data. Data collection techniques used are literature study methods, documentation studies and interviews. The data analysis method used is quantitative method, namely normality test, heteroscedasticity test, multicollinearity test, autocorrelation test, multiple linear regression analysis, correlation coefficient and determination, f test and t test. Based on the results of the Hypothesis Testing research and discussion, it was obtained that Debt to Equity Ratio and Current Ratio simultaneously had a positive and significant effect on Net Profit Margin. The results of the Hypothesis Testing Debt to Equity Ratio partially have a positive and significant effect on Net Profit Margin. Hypothesis Test Results Current Ratio partially has no positive and significant effect on Net Profit Margin.